2011
DOI: 10.1071/rd10345
|View full text |Cite
|
Sign up to set email alerts
|

Study of the proacrosin - acrosin system in epididymal, ejaculated and in vitro capacitated boar spermatozoa

Abstract: The present study aimed to develop a set of sensitive assays to evaluate the presence of different isoforms, the activity degree, and the immunolocalisation of proacrosin-acrosin in sexually mature boars. The goal was to determine the proacrosin-acrosin status of boar spermatozoa throughout epididymal maturation, during ejaculation and after in vitro capacitation. In epididymal samples, proacrosin expression was high in all regions studied. In contrast, α- and β-acrosin expression was low in the caput region, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 46 publications
5
21
0
Order By: Relevance
“…As acrosin at the time was supposed to play a role in sperm-zona penetration, the sperm proteolytic activity was first analyzed by digestion of a gelatin substrate: lysis diffused around reacted acrosomes and disappeared after head denudation (GaddumRoss and Blandau 1977). Confirming earlier studies, Puigmule et al (2011) observed by immunoelectron microscopy the proacrosin-acrosin complex and a metalloproteinase concentrated in the AR of in vitro capacitated boar spermatozoa, both originating from the proacrosomic granule; acrosin was also detected, almost uniformly, in the AS of epididymal bull spermatozoa, with the notable exception of the DBs, not pointed out by the authors (Ferrer et al 2012). Equatorin, a glycoprotein bound to the acrosomal membrane of round spermatids, was later associated with the OAM (except in the apical region) and IAM on one side and the underlying acrosomal material on the other side in mouse spermatozoa (Ito et al 2013); it is externalized during the acrosome reaction (Yoshida et al 2010), however, its role in fertilization is yet to be determined.…”
Section: Distribution Of Components In the Intact Acrosomesupporting
confidence: 89%
“…As acrosin at the time was supposed to play a role in sperm-zona penetration, the sperm proteolytic activity was first analyzed by digestion of a gelatin substrate: lysis diffused around reacted acrosomes and disappeared after head denudation (GaddumRoss and Blandau 1977). Confirming earlier studies, Puigmule et al (2011) observed by immunoelectron microscopy the proacrosin-acrosin complex and a metalloproteinase concentrated in the AR of in vitro capacitated boar spermatozoa, both originating from the proacrosomic granule; acrosin was also detected, almost uniformly, in the AS of epididymal bull spermatozoa, with the notable exception of the DBs, not pointed out by the authors (Ferrer et al 2012). Equatorin, a glycoprotein bound to the acrosomal membrane of round spermatids, was later associated with the OAM (except in the apical region) and IAM on one side and the underlying acrosomal material on the other side in mouse spermatozoa (Ito et al 2013); it is externalized during the acrosome reaction (Yoshida et al 2010), however, its role in fertilization is yet to be determined.…”
Section: Distribution Of Components In the Intact Acrosomesupporting
confidence: 89%
“…Many of the identified SP-proteins show catalytic activity, specifically hydrolase activity, and some of them would also indirectly be related with reproductive functions, as occurs with Acrosin. It is known that Acrosin is involved in the proacrosinacrosin system necessary for boar sperm capacitation [26]. Cathepsins (Pro-cathepsin H, Cathepsin L1, Cathepsin H, Cathepsin Z and Cathepsin D) are also SP-proteins with hydrolase activity, specifically protease activity, some secreted in the epididymis [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Acrosin activity in extended and frozen-thawed sperm samples was determined according to the method of Langlois et al (2005) and modified by Puigmulé et al (2011). In the case of frozen-thawed spermatozoa evaluated at 30 and 240 min after thawing, samples were first centrifuged for 5 min at 158C and 600g, resuspended in phosphate-buffered saline (PBS) and the concentration adjusted to 2 Â 10 7 spermatozoa mL À1 .…”
Section: Evaluation Of Acrosin Activitymentioning
confidence: 99%